India's National Digital Health Mission - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
India is using Information and Communication Technologies (ICTs) to leapfrog economic development in key sectors: health, education, infrastructure, finance, agriculture, manufacturing, and perhaps most important, governance. In doing so, India is increasing Internet penetration by increasing Internet subscribers and digital literacy. These have acted as the key drivers for the Indian Government to envision digitalization in its various sectors including health care. The Government of India laid emphasis on digitalization in India's healthcare sector in its National Health Policy, 2017. The National Digital Health Blueprint, 2019 recognized the need to put together a National Digital Health Mission (NDHM) which can act as the foundation on which national digital health ecosystem can be built. On the nation's 74th Independence Day, the Government of India embarked on its journey to achieve Universal Health Coverage by launching the National Digital Health Mission. NDHM intends to create a holistic and comprehensive digital health ecosystem that will lay the foundation of a strong public digital infrastructure, digitally empower individuals, patients, doctors, health facilities, and help streamline the delivery of healthcare services and related information. However, it is important to emphasize that the success of NDHM is dependent on its adoption by the centre and states, by public and private entities and by individuals and decision makers. It is also crucial to analyse international experiences in order to learn from their achievements and mistakes.
Keywords: 330